Repositioning Yunnan: security and China's geoeconomic engagement with Myanmar. Issue 2 (3rd August 2016) - Su, Xiaobo
ABSTRACT: China's geoeconomic engagement with Myanmar derives from three Myanmar-related security concerns (social security along the Yunnan–Myanmar border, economic security for the global expansion of Chinese capital and energy security). To facilitate this engagement, Yunnan is repositioned as a strategic bridgehead. To understand this geoeconomic engagement, this paper examines two specific transnational projects: Yunnan's agricultural investment in northern Myanmar; and the Sino-Myanmar oil and gas pipelines. The construction of Yunnan as a bridgehead shows that the Chinese state incorporates economic rationale into geopolitical concern with Myanmar. Through Yunnan's geoeconomic repositioning, the Chinese state hopes to build a China-oriented transnational network of production and consumption which includes Yunnan and neighbouring countries.